HeartFull: Feasibility of an Integrated Program of Care for Patients with Advanced Stage of Heart Failure. (October 2022) - Steinberg, Leah; Isenberg, Sarina R.; Mak, Susanna; Meaney, Christopher; Lokuge, Bhadra; Arvanitis, Jennifer; Goldman, Russell; Wegier, Pete; Husain, Amna F.
Introduction: Patients at an advanced stage of heart failure (AHF), specifically chronic severe symptomatic heart failure defined as New York Heart Association III/IV with hospitalization in the year prior, have high mortality, healthcare utilization, and low palliative care involvement. Objectives: The primary objectives were to determine the feasibility of recruiting patients and engaging cardiology and palliative healthcare providers in a program of integrated care for AHF (HeartFull); the proportion of patients who died in non-acute care settings. Secondary objectives were to describe patient-reported outcomes and pre-post comparison of healthcare utilization. Methods: Patients were recruited from an urban academic hospital with expert heart failure care and a 24/7 inpatient and home palliative service. Utilization, disposition, and surveys were collected monthly for up to 20 months. Results: Of 46 patients referred, 30 (65%) agreed to participate, 27 died during the study period, 19 (70%) died in non-acute care settings, while 8 (30%) died in hospital. We found no significant difference in pre- and post-intervention rates of hospitalization (RR .715; CI .360, 1.388; P = .3180), nor emergency visits (RR .678; CI .333, 1.338; P = .2590), but both trended downward. No significant changes were observed in patient-reported outcomes. Conclusion: In an urban academic hospital with palliative care, it was feasible to implement an integrated program for AHF. Patients died at home or in a palliative care unit at rates similar to palliative oncology patients and at higher rates than the general AHF population. HeartFull is now part of clinical practice.